In Vitro Digestibility of Plastein Gel Prepared from Peptic Digest of Casein - Suwedo Hadiwiyoto; Richard D King (Indonesian Food and Nutrition Progress, 1994)
In vitro digestibility of plastein prepared from casein hydrolyzate was evaluated using proteolytic enzymes. Pancreatin was the most effective digestion enzyme, followed by trypsin, α-chymotrypsin, and pepsin was the least effective. The in vitro digestibility of plastein was higher than that of casein. Amino acid analysis of plastein showed that plastein was rich in glycine, leucine, methionine, and histidine. The amino acid pattern of plastein was remarkably similar to FAO/WHO/UNU standard for amino acid requirements.